Abraham Lincoln Papers at the Library of Congress : Collection - Library of Congress - Office of the Director for Area Studies (2021)
"The papers of Abraham Lincoln (1809-1865), lawyer, representative from Illinois, and sixteenth president of the United States, contain approximately 40,550 documents dating from 1774 to 1948, although most of the collection spans from the 1850s through Lincoln’s presidency (1861-1865). Roughly half of the collection, more than 20,000 documents, comprising 62,000 images, as well as transcriptions of approximately 10,000 documents, is online. Included on this website in their entirety are Series 1-3 of the Lincoln Papers and the original materials in Series 4. Excluded from this online presentation is a sizeable portion of Series 4, which consists of printed material and reproductions of government and military documents made from originals in the holdings of the National Archives and Records Administration.“ [self-description]